Optimal leniency programs - Giancarlo Spagnolo (Fondazione Eni Enrico Mattei (FEEM), 2000)
Leniency programmes reduce sanctions for law violators that self-report. We focus on their ability to deter cartels and organised crime in general by increasing incentives to "cheat" on partners. Moderate leniency programmes that reduce/cancel sanctions for the reporting party cannot affect organised crime. Courageous leniency programmes that reward self-reporting parties may completely and costlessly deter it. When fines/rewards are pure transfers, optimal leniency programmes maximise rewards for self-reporting. When financing rewards are costly, optimal leniency programmes are restricted to the first reporting party, and make this residual claimant for the fines paid by the others.
Keywords: K42; K21; 330; Self reporting; law enforcement; antitrust; cartel deterrence; crime deterrence; organised crime; collusion; corruption; illegal trade; Strafrecht; Rechtsökonomik; Kartell; Organisierte Kriminalität; Korruption; Theorie